The Influence of Product Quality and Price Perception on Repurchase Intention at Favehotel Olo Padang - Karin Gifa Ananta Sari; Rahmi Fadilah (Journal of Multidimensional Management, 2026)
The Indonesian hospitality industry is experiencing rapid growth, intensifying competition among hotels. This study examines the influence of product quality and price perception on repurchase intention at Favehotel Olo Padang. Using a quantitative associative approach, data were collected from 100 guests through questionnaires measured on a Likert scale. The analysis employed multiple linear regression using SPSS version 26.00. Results indicate that product quality and price perception together significantly influence repurchase intention (F = 6.323, p = 0.003). Individually, price perception shows a significant positive effect (t = 2.178, p = 0.032), while product quality does not demonstrate significant influence (t = 1.967, p = 0.052). The coefficient of determination reveals that both variables explain 11.5% of repurchase intention variation, with the remaining 88.5% influenced by other factors. These findings suggest hotel management should prioritize competitive pricing strategies while maintaining product quality standards to enhance guest retention and loyalty.